GERMAS BERLIAN: GERAKAN MASYARAKAT BERDAYAKAN KELUARGA UNTUK IBU DAN ANAK DENGAN PENDEKATAN NEUROBEHAVIOUR, SOSIAL, DAN BUDAYA - Fitria Jannatul Laili; Megawati, Megawati; Vonny Khresna Dewi; Rafidah, Rafidah; Erni Yuliastuti; Nur Rohmah Prihatanti; Efi Kristiana; Isnaniah, Isnaniah; Zakiah, Zakiah; Khairir Rizani; Suryanti, Suryanti (Bajang Institute, 2025)
The Cempaka Subdistrict in Banjarbaru City faces several maternal and child health challenges, including low awareness of clean and healthy living behaviors, limited antenatal care visits, anemia among pregnant women and adolescents, suboptimal exclusive breastfeeding practices, incomplete basic immunization, and inadequate neonatal care knowledge. These problems are compounded by limited access to health services and varying levels of health literacy within the community. This community service program, Germas Berlian (Community Movement to Empower Families for Maternal and Child Health through Neurobehavioral, Social, and Cultural Approaches), aims to enhance community knowledge, skills, and health practices across the life cycle. The activities included coordination and field observation, Focus Group Discussions (FGD), integrated health education, health screenings for pregnant women, adolescents, and toddlers, capacity-building training, and home visits for prioritized families. Post-intervention evaluations demonstrated significant improvements in participants’ knowledge, nutritional awareness, health practices, and screening outcomes. The program highlights the effectiveness of integrated and culturally appropriate educational interventions to empower families and improve maternal and child health in underserved areas.